Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1021/acsami.9b10479
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium Sulfide Nanoparticles as a Biosafe Spectral CT Contrast Agent for Gastrointestinal Tract Imaging and Tumor Theranostics in Vivo

Abstract: Spectral computed tomography (CT) imaging as a novel imaging technique shows promising prospects in the accurate diagnosis of various diseases. However, clinically iodinated contrast agents suffer from poor signal-to-noise ratio, and emerging heavy-metal-based CT contrast agents arouse great biosafety concern. Herein, we show the fabrication of rhenium sulfide (ReS2) nanoparticles, a clinic radiotherapy sensitizer, as a biosafe spectral CT contrast agent for the gastrointestinal tract imaging and tumor therano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…Nanoparticles, generally characterized by submicronic (<1 µm) systems of metallic or organic materials, offer broad applications in various fields including tumor detection, imaging, diagnosis and treatment 56 . Several types of nanoparticles, such as carbonaceous, Prussian blue, or paramagnetic nanoparticles are available for in vitro diagnosis based on their peroxidase-like activity or function as enzyme carriers 57 , 58 and in vivo diagnosis as carriers of contrast agents 59 , 60 . In addition to diagnosis, their current applications in cancer treatment have gained widespread interest.…”
Section: Discussionmentioning
confidence: 99%
“…Nanoparticles, generally characterized by submicronic (<1 µm) systems of metallic or organic materials, offer broad applications in various fields including tumor detection, imaging, diagnosis and treatment 56 . Several types of nanoparticles, such as carbonaceous, Prussian blue, or paramagnetic nanoparticles are available for in vitro diagnosis based on their peroxidase-like activity or function as enzyme carriers 57 , 58 and in vivo diagnosis as carriers of contrast agents 59 , 60 . In addition to diagnosis, their current applications in cancer treatment have gained widespread interest.…”
Section: Discussionmentioning
confidence: 99%
“…Mortezazadeh confirmed in vitro cell experiments that nanocontrast agents can improve MR imaging quality without increasing cytotoxicity [20]. Some other researches have stated that the signal-to-noise ratio of rhenium sulfide nanoparticle contrast agent is higher than that of iodine contrast agent, and the use of rhenium sulfide nanoparticle contrast agent in CT imaging can improve the contrast of gastrointestinal imaging in patients [21]. At present, the common CTA nanocontrast agents include nano suspensions, micelles, and nano latexes [22][23][24].…”
Section: Discussionmentioning
confidence: 88%
“…For example, when using iodine contrast agents, patients need to use nephrotoxic drugs, mannitol, diuretics, and other drugs for the disease. Wang et al confirmed in his research that the signal-to-noise ratio of iodine contrast agent is relatively poor, and there are certain biological safety risks [22]. Therefore, finding new and effective CT contrast agents has become the focus of research by many scholars and clinicians.…”
Section: Analysis Of Consistency Between Ct and Postoperativementioning
confidence: 99%